Enriching the Energy Efficiency using Enhanced Virtual Grid Algorithm (EVGA) in Large Scale Wireless Sensor Network (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless sensor network is extensively worn to check the spot (or) region. Diminutiveamount of nodes are deployed to sense, transmit the information. To augment the lifespan of nodes, different types of routing algorithm are used. Grid structure aids to getbetter lifetime of the network by partition the spot into number of grids. The proposedmethod helps to beat the issues to loss the energy at the time of transmitting the data fromSensor Nodes (SN) to Cluster Head (CH) and to the Base Station (BS). Virtual grid recitalfacilitates to boost the energy by energy consumption. It supports to broadcast the dataquickly. BS carries out the entire task resembling cluster head selection, cluster formation,Grid formation and isolated node recognition etc. Each cell is divided into equal numberof cells in grid and it allows to communicating the node for data transmission easily usingshortest path algorithm. EVGA proves it increases the lifetime of the node and itconsumes energy.